Media Framing Strategy in Coverage of the 2024 Mandailing Natal Regency Election - Farid, Ahmad Salman (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
The 2024 Mandailing Natal Regency Election has become a political contest that has captured the attention of various local online media outlets. Media play a crucial role in shaping public perception through news framing, which can influence the political preferences of the community. This study employs a qualitative method with a framing analysis approach. Data were collected from nine news articles from each online media outlet published during the campaign period up to post-election. The analysis was conducted by identifying the framing elements according to Entman, namely problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings indicate that the three media outlets frame the coverage of the Sahata and On Ma candidate pairs differently. MohgaNews.co.id frames Sahata positively as an experienced pair close to the community, focusing on social stability. StartNews.co.id emphasizes the importance of election security and harmony, presenting the candidates neutrally. Meanwhile, MadinaPos.com prioritizes the aspects of legality and legal certainty in its reporting, with significant attention to the candidates’ administrative compliance. The differing frames across the three media reflect their respective agendas in influencing public perception. MohgaNews.co.id tends to support the incumbents, StartNews.co.id highlights security as a key issue, while MadinaPos.com emphasizes a fair and lawful electoral process. These findings demonstrate that media have a significant influence in shaping local political narratives, which can impact election outcomes and public participation.